1997
DOI: 10.1016/s0167-4889(97)00032-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extremely low frequency (ELF) magnetic field exposure on morphological and biophysical properties of human lymphoid cell line (Raji)

Abstract: Human B lymphoid cells (Raji) were exposed for 72 h to a 50 Hz sinusoidal magnetic field at a density of 2 milliTesla (rms). The results of exposure showed a decrease in membrane fluidity as detected by Laurdan emission spectroscopy and DPH fluorescence polarization. Field exposure also resulted in a reorganization of cytoskeletal components. Scanning electron microscopy (SEM) revealed a loss of microvilli in the exposed cells. This change in plasma membrane morphology was accompanied by a different actin dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 34 publications
6
69
1
2
Order By: Relevance
“…In development of HVA, Sinensky (Sinensky, 1974) observed using Electron Spin Resonance (ESR) that the order parameter of E. coli membranes remained constant, determined as a function of spin probe rotational correlation time, despite their phospholipid compositions changing in response to different growth temperatures. Subsequently, evidence for HVA as a conserved evolutionary mechanism emerged (Behan-Martin et al, 1993;Cossins and Prosser, 1978) and HVA has since been reported under many other changing environmental conditions, such as in response to hydrostatic pressure (Behan et al, 1992;Macdonald, 1986, 1984), osmotic pressure (Laroche et al, 2001) , low magnetic field strength (Santoro et al, 1997) and chemicals such as PCB-153 (Gonzalez et al, 2013), mitelfosine (Rybczynska et al, 2001) and crude oil (Mazzella et al, 2005). To date evidence for HVA has been found in species across the three domains of life and it is arguably the most widely used theory to explain phospholipid compositional changes, usually through the concept of maintaining membrane fluidity or membrane viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…In development of HVA, Sinensky (Sinensky, 1974) observed using Electron Spin Resonance (ESR) that the order parameter of E. coli membranes remained constant, determined as a function of spin probe rotational correlation time, despite their phospholipid compositions changing in response to different growth temperatures. Subsequently, evidence for HVA as a conserved evolutionary mechanism emerged (Behan-Martin et al, 1993;Cossins and Prosser, 1978) and HVA has since been reported under many other changing environmental conditions, such as in response to hydrostatic pressure (Behan et al, 1992;Macdonald, 1986, 1984), osmotic pressure (Laroche et al, 2001) , low magnetic field strength (Santoro et al, 1997) and chemicals such as PCB-153 (Gonzalez et al, 2013), mitelfosine (Rybczynska et al, 2001) and crude oil (Mazzella et al, 2005). To date evidence for HVA has been found in species across the three domains of life and it is arguably the most widely used theory to explain phospholipid compositional changes, usually through the concept of maintaining membrane fluidity or membrane viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was confirmed by electron microscope finding of multiple electron lucent secretory granules in ELF-MF exposed group (Figure 3 B). Santoro et al [27] found that EMFs interfere with protein phosphorylation and modify the plasma membrane structure and interfere with the initiation of the signal cascade pathways for protein synthesis. They also observed that decreased protein content may be due to ruptured cellular organoids.…”
Section: Resultsmentioning
confidence: 99%
“…Cambios semejantes han sido reportados con el uso de diversos campos magnéticos, pulsantes o constantes, en cultivos celulares tanto en células adherentes como no adherentes (8,9,10,11,12). En nuestro estudio, sin embargo, no se apreciaron cambios morfológicos en las células no adherentes K-562 (eritroleucemia humana) Los cambios que han sido descritos por la exposición a campos magnéticos moderados (6mT) consisten, para el caso de células que crecen en suspensión, en la pérdida de su forma redondeada y en la adquisición de una alargada e irregular, mientras que para las células adherentes se trata de modificaciones en su forma y orientación o en la pérdida de su adherencia, quedando, de esta manera, libremente suspendidas en el cultivo (13).…”
Section: Discussionunclassified